2016
DOI: 10.1002/jbm.b.33637
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of chitosan—Polyethylene glycol‐polyvinylpyrrolidone‐coated superparamagnetic iron oxide nanoparticles as carrier system: Drug loading and in vitro drug release study

Abstract: In the present research work, the anticancer drug "curcumin" is loaded with Chitosan (CS)-polyethylene glycol (PEG)-polyvinylpyrrolidone (PVP) (CS-PEG-PVP) polymer nanocomposites coated with superparamagnetic iron oxide (Fe3 O4 ) nanoparticles. The system can be used for targeted and controlled drug delivery of anticancer drugs with reduced side effects and greater efficiency. The prepared nanoparticles were characterized by Fourier transmission infrared spectroscopy (FTIR), vibrating sample magnetometry (VSM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Alternative drugs may also be linked to nanosystems. Curcumin, a natural polyphenolic hydrophobic compound from Curcuma longa rhizomes, has been incorporated into IONPs for preventing and fighting cancer [ 10 , 106 , 133 , 173 , 174 , 175 ]. It is believed that this herbal product remains captured at the hydrophobic interface between components of surfactant-stabilized nanocarriers [ 133 ].…”
Section: Drugs Bound To Ionpsmentioning
confidence: 99%
“…Alternative drugs may also be linked to nanosystems. Curcumin, a natural polyphenolic hydrophobic compound from Curcuma longa rhizomes, has been incorporated into IONPs for preventing and fighting cancer [ 10 , 106 , 133 , 173 , 174 , 175 ]. It is believed that this herbal product remains captured at the hydrophobic interface between components of surfactant-stabilized nanocarriers [ 133 ].…”
Section: Drugs Bound To Ionpsmentioning
confidence: 99%
“…The reduction of saturation magnetization of MNPs after polymeric encapsulation has already been reported in the literature. Santos et al (2018), [8] Prabha and Raj (2016), [45] and Batch et al (2012) [46] observed a reduction of 50%, 41%, and 49% in the saturation magnetization of MNPs after encapsulation in poly(thioether-ester), chitosan and, PMMA NPs, respectively. The superparamagnetic profile is es- sential for MNPs to exert hyperthermic effects and to be directed to specific targets.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the release rate was controlled mostly by drug diffusion rather than polymeric dissolution. Thus, even when drugs are incorporated in a water-soluble matrix which will be subjected to erosion, the rate-limiting step is diffusion of the drug out of the matrix [9,[35][36][37].…”
Section: The Embedded Matrix Principlementioning
confidence: 99%